Stochastic Programming and Decision Analysis: An Apparent Dilemma - Blau, Roger A. (Management Science, 1974)
An example is given which demonstrates that using a decision theory analysis for the basic chance-constrained model of stochastic linear programming may lead to an apparent dilemma, namely, 0 > EVSI > EVPI. The problem is discussed and a resolution suggested.